2007
DOI: 10.1084/jem.20071094
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of epidermal hyperplasia by TNF inhibition is associated with reduced Th17 responses

Abstract: Biological agents have dramatically improved treatment options for patients with severe psoriasis. Etanercept (tumor necrosis factor [TNF] receptor–immunoglobulin fusion protein) is an effective treatment for many psoriasis patients, and blockade of TNF is considered to be its primary action. However, in this clinical trial, we show that etanercept has early inhibitory effects on a newly appreciated type of T cells: T helper type 17 (Th17) cells. Etanercept reduced the inflammatory dendritic cell products that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
582
0
14

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 614 publications
(634 citation statements)
references
References 51 publications
38
582
0
14
Order By: Relevance
“…Anti-TNF may directly inhibit Th17 through its known inhibitory effects on IL-1 and IL-6 production in RA [24]. Indeed etanercept, another anti-TNF agent, has been shown to inhibit Th17 cells in patients with psoriasis [25]. Therapy with infliximab has also been associated with a reduction in the rate of Treg apoptosis in patients with RA [26], although it is unclear whether this is a direct effect or indirectly perhaps through the alteration of the cytokine milieu.…”
Section: Cytokine Blockade As a Methods Of Targeting Treg In Patients mentioning
confidence: 99%
“…Anti-TNF may directly inhibit Th17 through its known inhibitory effects on IL-1 and IL-6 production in RA [24]. Indeed etanercept, another anti-TNF agent, has been shown to inhibit Th17 cells in patients with psoriasis [25]. Therapy with infliximab has also been associated with a reduction in the rate of Treg apoptosis in patients with RA [26], although it is unclear whether this is a direct effect or indirectly perhaps through the alteration of the cytokine milieu.…”
Section: Cytokine Blockade As a Methods Of Targeting Treg In Patients mentioning
confidence: 99%
“…Therefore, cytokines Th17 stimulate the keratinocytes to proliferate and to produce inumerous inflammatory proteins (Pic.1). 1,5,7,8 The proliferation of LTh1 induced by IL-12 leads to the production of TNF-α and INF-γ. The INF-γ also stimulates the production of IL-12, IL-8, IP-10, IL-23, defensins and iNOS by the keratinocytes and DC.…”
Section: Immunopathogenesis Of Psoriasismentioning
confidence: 99%
“…The INF-γ also stimulates the production of IL-12, IL-8, IP-10, IL-23, defensins and iNOS by the keratinocytes and DC. [7][8] Interferons, TNFs and IL-20 are activators of transcription factors (STAT-1, STAT-3 and nuclear factor κB) that, in their turn, control various groups of genes that codify various inflammatory mediators in psoriasis. 1,5,9 Recent studies in patients treated with etanercept reveal that the TNF modulates the activation and maturation of the DCs in psoriasis.…”
Section: Immunopathogenesis Of Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…63 However, the role of IL-17 in cutaneous wound healing, and whether it is produced by skin cd T cells, are less clear. Here, Büchau and colleagues reported that cultured skin cd T cells rapidly produce IL-17A upon TCR activation.…”
Section: Function In Tissue Repair and Inflammationmentioning
confidence: 99%